Peculiarities Of Developing Students’ Communicative Abilities During Educational Process - Baydullayeva Firuza Akilbekovna (Genius Journals, 2022)
The article deals with the issues based on developing students’ communicative abilities in the educational process. As we know, communication skills play an important role in professional activity; they are one of the factors of effective communication. The development of communication skills must be improved through the formation of communication skills that underlie professional activity. The spontaneous formation of communicative skills often leads to an authoritarian style of behavior, the emergence of private conflict situations, tension in the relationship between the teacher and the students, a decline in academic performance, an unwillingness to learn, mental trauma and irreparable losses in moral education, and often to asocial behavior of students.
Keywords: Communicative Skills; Communication; Behavior Of Students; Personality-Oriented Approach